Transformasi Komunikasi dan Akselerasi Infrastruktur Digital Menuju Era Masyarakat Informasi Indonesia - Abdul Gafar (Jurnal Riset Informatika dan Inovasi, 2026)
The revolution of digital technology has fundamentally altered social interaction patterns by introducing new mediums that facilitate the massive distribution of information. The emergence of new media has triggered a significant shift in lifestyles toward a digital ecosystem, particularly regarding information consumption behavior. This rapid flow of data marks a transition into the era of the information society. The sustainability of this era is highly dependent on the availability of robust Information and Communication Technology (ICT) infrastructure, making government efforts to accelerate digital access crucial. Ultimately, inclusive access empowers public participation in driving social change through more open feedback communication mechanisms.